Rising floodwaters: mapping impacts and perceptions of flooding in Indonesian Borneo - Wells, J.A.; Wilson, K.A.; Abram, N.K.; Nunn, M.; Gaveau, D.L.A.; Runting, R.K.; Tarniati, N.; Mengersen, K.L.; Meijaard, E. (IOP Publishing, 2016)
The roles of forest and wetland ecosystems in regulating flooding have drawn increasing attention in the contexts of climate change adaptation and disaster risk reduction. However, data on floods are scarce in many of the countries where people are most exposed and vulnerable to their impacts. Here, our separate analyses of village interview surveys (364 villages) and news archives (16 sources) show that floods have major impacts on lives and livelihoods in Indonesian Borneo, and flooding risks are associated with features of the local climate and landscape, particularly land uses that have seen rapid expansions over the past 30 years. In contrast with government assessments, we find that flooding is far more widespread, and that frequent, local, events can have large cumulative impacts. Over three years, local news agencies reported floods that affected 868 settlements, 966 times (including 89 in urban areas), inundated at least 197 000 houses, and displaced more than 776 000 people, possibly as many as 1.5 million (i.e. 5%–10% of the total population). Spatial analyses based on surveys in 364 villages show that flood frequency is associated with land use in catchment areas, including forest cover and condition, and the area of wetlands, mines (open-cut coal or gold mines), and oil palm. The probability that floods have become more frequent over the past 30 years was higher for villages closer to mines, and in watersheds with more extensive oil palm, but lower in watersheds with greater cover of selectively-logged or intact forests. We demonstrate that in data-poor regions, multiple sources of information can be integrated to gain insights into the hydrological services provided by forest and wetland ecosystems, and motivate more comprehensive assessment of flooding risks and options for ecosystem-based adaptation.